Ministerial Decree No. 436/2016 Concerning the Amendment of the Sale Prices of the Electric Energy and Customer Service Charge of the year 2016/2017 = قرار وزاري رقم 436 لسنة 2016 بشأن تعديل أسعار بيع الطاقة الكهربائية ومقابل خدمة العملاء لعام 2016/2017 / Prime Minister. - Egypt. Prime Minister (2025)
ministerial decree no. 436 of the year 2016 issued on 8/8/2016 – قرار وزارى رقم 436 لسنة 2016 صادر بتاريخ 8/8/2016